Pelatihan Pemanfaatan Limbah Plastik Menjadi Eco-Paving Block Di Desa Karangluas - Juanita Jihan Kamila; Salma Alvita; Muhammad Muhajir; Rahmadi Yotenka (Jurusan Matematika FMIPA Universitas Pattimura, 2025)
The challenge of plastic waste management persists in several nations, including Indonesia. Society's increasing use of plastic garbage exacerbates this issue. Karangluas village faces challenges in managing plastic garbage. Consequently, this community service initiative offers a solution for the conversion of plastic garbage into eco-paving blocks. The methodology employed in the training activity includes the preparatory phase to ascertain community issues and requirements through interviews, surveys, and observations. The implementation stage encompasses the production of eco-paving blocks, beginning with trash sorting and culminating in the fabrication of the paving blocks. This initiative aims to mitigate environmental and waterway pollution while enhancing the comprehension and economic welfare of the Karangluas village community.